A Test of the AICPA Differentiation between Stock Dividends and Stock Splits - Chottiner, Sherman; Young, Allan (Journal of Accounting Research, 1971)
In 1968, a record number of 276 companies listed on the New York and American Stock Exchanges split their shares or made a stock distribution of at least 20%. The previous all-time high was 193 in 1966 (compared to only 151 in 1967). The recent decline in economic activity and corporate profits has also motivated some managements to omit their cash dividends and make stock distributions instead. The trend toward greater stock distributions calls attention to the importance of the accounting treatment for such transactions. In chapter 7B of its Accounting Research Bulletin No. 43,1 the AICPA distinguishes common stock distributions which should be considered stock dividends from those which should be considered stock splits. The AICPA guideline is that distributions below 20% to 25% should ordinarily be recorded as dividends, while those above this range should ordinarily be recorded as splits.2 This division supposedly meets the different purposes of stock dividends and stock splits and is based on observations of market price action related to stock dividends and stock splits. The purpose of this paper is to report on one type of statistical test which might be used to verify the 20-25% guideline.